Curating the sexual health of a nation : misrepresentations of sexual health, STIs and HIV/AIDS from the colonial to the post-colonial - Muhammad Zaqeer Mohd Radz (Nanyang Technological University, 2020)
In Gender, Sexuality, and the State in Southeast Asia, Michael Peletz talked about the idea of “graduated pluralism” which highlights the differential distribution that encourages certain groups to nurture and reproduce, while specifically excluding “others” from participation. To examine the State’s “handling/mishandling” of the 1980s AIDS epidemic, I will be borrowing some of Peletz’s ideas to look into how such state actions may have shaped ideas about Gender and Sexuality during the time. Additionally, while scholars like Lenore Manderson have attempted to trace back the history of sexually transmitted diseases to the times of British Malaya, and while much of the recent scholarship around HIV/AIDS pertaining to Singapore focuses on the biological factors for the progression of AIDS amongst HIV patients, the sexual behaviors of individuals and medicinal studies. The literature that specifically talks about the social histories of Gender, Sexuality and Queer Representation in 20th Century Singapore in lieu of the AIDS epidemic is severely lacking. By analyzing sources such as posters, public statements made by the Ministry of Health, media coverage, local television programming, oral sources, and secondary literary works, I hope to answer some of my current working research questions ie; “Historically, how has Gender and Sexuality been understood, represented and framed within the context of the 1980s HIV/AIDS epidemic in SG? And how did the state react and what was the public perception of the epidemic at the time and has it changed?”